2018
DOI: 10.1101/470823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanoscale decompaction of nucleosomal DNA revealed through multi-color super-resolution microscopy

Abstract: Super-resolution imaging of histones and DNA reveals that DNA is compacted by groups of nucleosomes -clutches -at the nanoscale level and clutch compaction of DNA is affected by histone tail acetylation especially in highly folded regions containing several nearby clutches. AbstractChromatin organization plays an important role in regulating gene expression. Previously, we showed that chromatin is organized in the form of nucleosome groups or clutches. The size and nucleosome packing density of clutches decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…These results are in line with a more folded chromatin confirmation in (−)TSA cells, which opens and decondenses after TSA treatment. These results are also consistent with recent super-resolution analysis, which showed that TSA-treated fibroblasts have small nucleosome nanodomains that are more uniformly distributed in the nuclear space compared to control fibroblasts (29,30). This decondensation was also confirmed in TSA-treated bovine mesenchymal stem cells (MSCs), where TSA treatment decreased the number and area of H2B nanodomains ( fig.…”
Section: Tsa Treatment Increases Nuclear Deformability and Migration supporting
confidence: 91%
See 1 more Smart Citation
“…These results are in line with a more folded chromatin confirmation in (−)TSA cells, which opens and decondenses after TSA treatment. These results are also consistent with recent super-resolution analysis, which showed that TSA-treated fibroblasts have small nucleosome nanodomains that are more uniformly distributed in the nuclear space compared to control fibroblasts (29,30). This decondensation was also confirmed in TSA-treated bovine mesenchymal stem cells (MSCs), where TSA treatment decreased the number and area of H2B nanodomains ( fig.…”
Section: Tsa Treatment Increases Nuclear Deformability and Migration supporting
confidence: 91%
“…S3C) and the infiltration depth measured on cross-sectional images using ImageJ. For scanning electron microscopy imaging, additional samples were fixed and dehydrated in ethanol (30,50,70, and 100%, 60 min per step) and then hexamethyldisilane for terminal dehydration under vacuum.…”
Section: Fabrication and Application Of A Poly(dimethylsiloxane) Migrmentioning
confidence: 99%
“…How might assembly of the deacetylase sub-complex with CHD4 to form intact NuRD influence transcription? Histone acetylation is thought to lead to a looser packing between nucleosomes and chromatin decompaction [61][62][63][64][65] , but here, by studying compaction in the immediate vicinity of the stably bound NuRD complex, we unexpectedly find that assembly of the intact NuRD complex leads to a more open chromatin structure where enhancers can diffuse faster and explore more of the nucleus (see Figure 5e). The chromatin decompaction and faster movement of enhancers in the presence of intact NuRD provides a molecular explanation for the increase in intermediaterange chromatin interactions (Figure 1b), the blurring of TAD and A/B compartment boundaries (Figure 1c), the increase in longer range enhancer-promoter interactions (Figure 1d), and the changes in enhancer interactions with promoters that are regulated by NuRD (Figure 1e).…”
Section: The Nurd Complex Modulates the Dynamics Of Enhancers To Control Transcriptionmentioning
confidence: 75%
“…The decrease in anomalous exponent unexpectedly suggests that in the absence of the intact NuRD complex chromatin is more condensed, whilst the diffusion coefficient and length of confinement show that CHD4 molecules diffuse more slowly and explore a smaller nuclear volume. We had expected to find that in the absence of deacetylation by NuRD, that the more acetylated chromatin would be decondensed [48][49][50][51][52] and that CHD4 would explore a greater nuclear volume. Notably, however, in the absence of MBD3 we observed a significant increase in the proportion of CHD4 molecules in the fast F2 state exhibiting directed motion (18 % vs 7.4 %, see Figure 3d, Extended Data Figure 10).…”
Section: The Holo-nurd Complex Modulates Chromatin Movement At Enhancmentioning
confidence: 99%
See 1 more Smart Citation